The Beneficial Effects of Vitamin D3 Against Trichloroethylene Toxicity in Rat Ovaries - Bagci, Helin; Melekoglu, Rauf; Celik Kavak, Ebru; Kuloglu, Tuncay; Simsek, Mehmet (Turkiye Klinikleri, 2020)
Objective: Vitamin D3 is an active metabolite of vitamin D and has been reported to have anti-oxidative effects due to inhibition of lipid peroxidation in some tissues both in vitro and in vivo studies. The current study was carried out to assess the protective effects of vitamin D3 on experimental trichloroethylene (TCE) toxicity in rat ovaries by using immunohistochemical detection of malondialdehyde (MDA) in tissues as well as histopathological scores' computation. Material and Methods: Twenty-four healthy rats were randomly divided into four equivalent groups: control (sham-operated), TCE+vitamin D3 (1000 mg/kg/day and 50 IU/day, in that order), TCE (1000 mg/kg/day), as well as vitamin D3 (50 IU/day). Histopathological and immunohistochemical analyses were carried out on tissue samples 21 days following exposure to vitamin D3 and TCE. Results: Histopathological examination showed a significant decrease of angiogenesis in the corpus luteum and a substantial degeneration in the ovarian follicles and germinal epithelium in ovarian tissues of TCE group. Also, immunohistochemical examination for MDA immunoreactivity revealed that MDA immunoreactivity was significantly increased in the TCE group compared to the control group. We observed that vitamin D3 administration improved histological parameters, which include follicular degeneration as well as germinal epithelium degeneration, limiting TCE's negative impacts on ovarian tissues. It was also confirmed that MDA immunoreactivity was considerably reduced in ovarian tissues in the TCE+vitamin D3 group. Conclusion: In this study, the significant improvements observed in immunohistochemical and histopathological tissue oxidative stress parameters indicate that treatment with vitamin D3 could be a conservative method to prevent ovarian TCE toxicity.
Keywords: Antioxidants; vitamin D3; ovary; oxidative stress; toxicity; trichloroethylene